Achieving Excellence in School Counseling through Motivation, Self-Direction, Self-Knowledge and Relationships. - Squier, Karl L. (SAGE Publications, 2014)
Your step-by-step handbook for results-based school counseling!This exciting new book by recognized school counseling experts describes a Construct-Based Approach (CBA) to school counseling that helps you: Design standards, deliver interventions, and evaluate year-long counseling strategies, action steps and measures within a CBA context Apply "research-based" standards to reflect student abilities, competencies, capabilities and skills Accurately assess student progress, proficiency and achievement Provide useful feedback to parents and students Includes in-depth analyses, a d